(untitled) (Applied Biological Research, 2018)
In present study the effect of oral administration of imidacloprid over two generations on the ovary of female Wistar rats was assessed. Female rats were divided into 3 groups. Group 1, as control, was given corn oil only while imidacloprid was administered in group 2 and 3 @ 10 and 20 mg kg-1 bw day 1, respectively. A disruption in estrous cyclicity was observed with a prolonged diestrous in both F1 and F2 generation. The weight of ovary decreased significantly in treated female rats of F2 generation. Histopathology of ovary of groups 2 and 3 revealed different stages of follicles. Percentage atresia of follicles was found higher in treated rat ovaries as compared to their respective control rats in both the generations. The results indicate that no observed effect level of imidacloprid for two generations female reproductive toxicity is 10 mg kg-1 bw day-1.